PENGATURAN CITY HOTEL BERKARAKTER CHAIN HOTEL SEBAGAI SALAH SATU BENTUK USAHA JASA PARIWISATA DI INDONESIA (STUDI KASUS DI BALI) - Made Suksma Prijandhini Devi Salain (University of Udayana, 2015)
Bali is one of the favorite tourism destinations in the world give benefits as well as loss for Indonesia and Bali particularly. As a tourism place, a lot of Hotels are established in Bali, especially the chain hotels, such as Aston, Ibis, Harris, Fave or Horrison Hotel. Existence of the chain hotels is causing unfair competition with the local hotels. They have different standards in competitive prices. Especially in Bali, there is no regulation that regulates the chain hotels. According to those conditions, it really need to conduct a normative research of the chain hotels regulations within international, national and local Balinese instruments.